До основних проблем домінантних субкультур: філософський аспект - Радзієвський, Віталій; Radzievskiy, Vitaliy (Східноєвропейський національний університет ім. Лесі Українки, 2016)
У статті досліджено питання субкультур у культурфілософському аспекті. Зокрема, порушено питання вивчення домінантних субкультур, а в їх складі – проблем парадигми філософії культури і загальної теорії та історії субкультур у постмодерному дискурсі.The article examines the issues of subcultures in the cultural and philosophical aspect. In particular, the author touches on the issues of the modern study of subcultures, and in their composition – problems of the paradigm of philosophy of culture and the general theory and history of subcultures in the postmodern discourse. The diversity and complexity of the structure of society contributes to the emergence of new socio-cultural processes and phenomena, the transformation of old forms, the philosophical rethinking and the acquisition of new values established concepts. The allocation subcultural as a separate line and the field of research of subcultures (at the level of the wider Humanities – general theory and history of subcultures) based on the dominant subcultures (subcultural mainstream and almost a second general cultural mainstream), which are a priority in the study of cultural space. In the article it is fair to say kulturpolitik main problems related to the comprehension of the dominant subcultures (subcultural question of analysis of evolution, theory of civilizations, marginalization, aesthetics, etc.).
To the Main Problems of the Dominant Subcultures: Philosophical Aspect
Keywords: філософія; естетика; філософія культури; домінантна субкультура; культура; маргінальні практики; philosophy; aesthetics; philosophy of culture; the dominant subculture